INNOVATIVE TEACHING STRATEGIES TO IMPROVE LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Devi Melani (SMART: Journal of Multidisciplinary Educational, 2024)
This study aims to identify and analyze innovative teaching strategies applied by elementary school teachers to improve student learning outcomes. Traditional teacher-centered approaches are increasingly inadequate in developing 21st-century skills such as critical thinking, collaboration, and problem-solving. Therefore, participatory and contextual teaching strategies are urgently needed to foster meaningful and active learning. A descriptive qualitative method was employed, using classroom observations, semi-structured interviews, and document analysis. The study was conducted at three semi-urban elementary schools (fictitious): SD Negeri Kreativa, SD Negeri Cendekia Bangunrejo, and SD Negeri Harapan Bangsa. Respondents included 9 classroom teachers (grades IV–VI), 3 school principals, and 45 students who directly participated in the observed learning processes. The findings indicate that the implementation of strategies such as project-based learning and problem-based learning positively affected students’ motivation, conceptual understanding, and social skills. Nevertheless, several structural challenges were identified, including time constraints, lack of teacher training, and administrative workload, which hindered consistent implementation. The novelty of this study lies in its micro-contextual approach at the elementary level, systematically linking innovative teaching strategies with measurable improvements in learning outcomes and 21st-century competencies. This research recommends strengthening institutional support and building teacher capacity to ensure the sustainability of pedagogical innovation in primary education.